Inside Back Cover: Kinetics‐Regulated Interfacial Selective Superassembly of Asymmetric Smart Nanovehicles with Tailored Topological Hollow Architectures (Angew. Chem. Int. Ed. 12/2022). Issue 12 (18th February 2022) - Xie, Lei; Liu, Tianyi; He, Yanjun; Zeng, Jie; Zhang, Wei; Liang, Qirui; Huang, Zilin; Tang, Jinyao; Liang, Kang; Jiang, Lei; Terasaki, Osamu; Zhao, Dongyuan; et al.
Abstract : A kinetics‐regulated cooperative polymerization induced interfacial superassembly strategy is used by Biao Kong and co‐workers in their Research Article (e202200240) to construct a series of asymmetric hollow porous composites with tunable diameters, architectures, and compositions. Owing to their excellent photothermal conversion performance and unique nanostructures, the resulting nanoparticles can be utilized as NIR light triggered nanovehicles with controllable cargo release.